VI Verano de la Investigación Científica de la Universidad de Guanajuato - Anaya Velázquez, Luis Fernando; Castillo Serrano, Ma. Soledad; Aragón Jáuregui, Carmen; Vargas Pacheco, Esperanza Rosaura (Acta Universitaria, 2000)
The sixth edition of the institutional program "Verano de la Investigación Científica de la Universidad de Guanajuato" (Scientific Research Summer of the University of Guanajuato) was held from July 3 to August 4, 2000, in which research results were compiled of 32 undergraduate students, 6 from State of Tabasco, financed by the Consejo de Ciencia y Tecnología del Estado de Tabasco (Sciences and Technology Council of Tabasco) and 26 from the Universidad de Guanajuato, supported by the University. The students selected belong to the following areas of learning: Social Sciences and Humanities, 6; Health, 4; Engineering, 5; Natural Sciences, 16; Economic Administration, 1.